Common Fixed Point Theorems Of Gregus Type For Compatible Mappings In Banach Spaces - Gupta, Neelmani (International Journal of Psychosocial Rehabilitation, 2009)
In this paper, we prove a common fixed point theorem of Gregus type for compatible mappings in Banach space. .Our work generalizes several earlier results on fixed points in this direction.